Targeting Insect Olfaction in vivo and in vitro Using Functional Imaging - Miazzi, Fabio; Jain, Kalpana; Kaltofen, Sabine; Bello, Jan E.; Hansson, Bill S.; Wicher, Dieter (Frontiers in Cellular Neuroscience, 2022)
Insects decode volatile chemical signals from its surrounding environment with the help of its olfactory system, in a fast and reliable manner for its survival. In order to accomplish this task, odorant receptors (ORs) expressed in olfactory sensory neurons (OSNs) in the fly’s antenna process such odor information. In order to study such a sophisticated process, we require access to the sensory neurons to perform functional imaging. In this paper, we present different preparations to monitor odor information processing in Drosophila melanogaster OSNs using functional imaging of their Ca2+ dynamics. First, we established an in vivo preparation to image specific OSN population expressing the fluorescent Ca2+ reporter GCaMP3 during OR activation with airborne odors. Next, we developed a method to extract and to embed OSNs in a silica hydrogel with OR activation by dissolved odors. The odor response dynamics under these different conditions was qualitatively similar which indicates that the reduction of complexity did not affect the odor response at OSN level.